Peran Kepemimpinan Islam dalam Meningkatkan Karakter dan Etos Belajar Siswa di Lembaga Pendidikan Islam - Muhammad Fauzan (Journal Islamic Education, 2024)
The function of leadership within Islamic educational institutions serves as a crucial element for the progression of these establishments. As a leader, every policy enacted will greatly influence the caliber of the staff. This study endeavors to analyze the leadership function within Islamic educational institutions utilizing a qualitative research approach. Data is collected through observations and interviews. The enactment of character education has been stipulated by Law Number 20 of 2003 regarding the National Instruction Framework, which asserts that "The capability of National education aims to cultivate skills and shape the character and cultural identity of individuals a worthy country to educate the nation’s life seeks to foster the potential of learners to become dependable individuals who submit to God Almighty". This research compiles data from a variety of pertinent literature sources, including academic databases, journals, books, and articles. The outcomes revealed that the leadership role within Islamic educational institutions holds substantial importance. Leaders in these organizations are tasked with possessing wisdom and local knowledge. They also supervise the administration of Islamic educational institutions, ensuring that the curriculum is in accordance with Islamic values, nurturing student character, and cultivating robust relationships with the community. Leaders are essential in improving the standard of education in Islamic educational institutions. They also play a significant part in fostering a more Islamic student character and reinforcing religious values while navigating the challenges and issues faced in managing Islamic education institutions, including curriculum-related concerns, financial issues, and the teaching staff.